2013
DOI: 10.1155/2013/806267
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stabilisation in the Treatment of Degenerative Disc Disease with Modic Changes

Abstract: Objective. Posterior dynamic stabilization is an effective alternative to fusion in the treatment of chronic instability and degenerative disc disease (DDD) of the lumbar spine. This study was undertaken to investigate the efficacy of dynamic stabilization in chronic degenerative disc disease with Modic types 1 and 2. Modic types 1 and 2 degeneration can be painful. Classic approach in such cases is spine fusion. We operated 88 DDD patients with Modic types 1 and 2 via posterior dynamic stabilization. Good res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…En este estudio la mayoría de los pacientes antes de someterse al procedimiento de estabilización dinámica fueron valorados con escala Modic dentro del tipo II y I, y a pesar de que esta condición persistió en el postquirúrgico no hubo correlación con evolución clínica y funcional favorables como en lo descrito por Olcay Eser. 13 Con el tema de artroplastía existe un reporte 14 con un seguimiento a cuatro años, en el que hay una mejora en las condiciones clínicas y radiográficas de los pacientes así como aumento de la altura del espacio intersomático; refiere una mejoría de 35% en escala de Oswestry. Nosotros observamos en este estudio que hubo una mejoría de 32.6%, siendo muy similar a lo reportado, pero con una disminución de la altura del espacio intersomático de 0.55 mm.…”
Section: Discussionunclassified
“…En este estudio la mayoría de los pacientes antes de someterse al procedimiento de estabilización dinámica fueron valorados con escala Modic dentro del tipo II y I, y a pesar de que esta condición persistió en el postquirúrgico no hubo correlación con evolución clínica y funcional favorables como en lo descrito por Olcay Eser. 13 Con el tema de artroplastía existe un reporte 14 con un seguimiento a cuatro años, en el que hay una mejora en las condiciones clínicas y radiográficas de los pacientes así como aumento de la altura del espacio intersomático; refiere una mejoría de 35% en escala de Oswestry. Nosotros observamos en este estudio que hubo una mejoría de 32.6%, siendo muy similar a lo reportado, pero con una disminución de la altura del espacio intersomático de 0.55 mm.…”
Section: Discussionunclassified
“…Hospital cost is also low than fusion operations. The dynamic stabilization instead of fusion also prevents the risks pseudoarthrosis and adjacent segment disease in these patients 3) . We believe that this procedure is suitable as an alternative surgical technique in patients who have degenerative spondylolisthesis or low-grade dysplastic type spondylolisthesis with radicular signs secondary to nerve root compression in decreased neural foramina.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that, in nonspecific low back pain (LBP), the prevalence of any type of Modic change was 46%, as opposed to 6% in the general population [ 10 13 ]. Most individuals with Modic changes of more than 90% on MRI will have back pain within one year [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%